Advances in metal–organic frameworks as adsorbents, photocatalysts and membranes: a new frontier in water purification - Moses Kiteto; Beryl Vidija; Cleophas Achisa Mecha; Register Mrosso; Martha N. Chollom (Discover Water, 2024)
Abstract Water is an essential and irreplaceable necessity for life on earth, sustaining ecosystems, nourishing agriculture and vital for human survival. However, increasing population and industrialization has exacerbated water scarcity and pollution. The Sustainable Development Goal 6 focuses on clean water and sanitation for all; thus, water purification and conservation are key priorities globally. Rampant pollution of water sources by emerging bio-recalcitrant contaminants, often deviant of conventional treatment methods, necessitates new approaches to water treatment. In this regard, metal organic frameworks (MOFs) are gaining prominence and offer solutions in versatile applications due to their unique structural characteristics and tunable properties. This review provides a comprehensive analysis of MOFs, covering their diverse structures, types, synthesis methods and characterization techniques. We explore the application of MOFs in water purification, as adsorbents, photocatalysts, and in membrane separation. The mechanism of operation of MOFs in each application is critically evaluated. The effect of the water treatment methods on energy consumption has also been investigated. We propose that for MOFs application in water treatment to be competitive and sustainable, there is need to address key issues such as synthesis of highly selective MOFs, recovery and reuse, scalability (pilot and industrial scale), and integration with existing water treatment technologies to create synergy. We provide future perspectives on these aspects.